Mitochondria: The ketogenic diet—A metabolism-based therapy. (June 2015) - Vidali, Silvia; Aminzadeh, Sepideh; Lambert, Bridget; Rutherford, Tricia; Sperl, Wolfgang; Kofler, Barbara; Feichtinger, René G.
Abstract: Mitochondria are the energy-producing organelles of the cell, generating ATP via oxidative phosphorylation mainly by using pyruvate derived from glycolytic processing of glucose. Ketone bodies generated by fatty acid oxidation can serve as alternative metabolites for aerobic energy production. The ketogenic diet, which is high in fat and low in carbohydrates, mimics the metabolic state of starvation, forcing the body to utilize fat as its primary source of energy. The ketogenic diet is used therapeutically for pharmacoresistant epilepsy and for "rare diseases" of glucose metabolism (glucose transporter type 1 and pyruvate dehydrogenase deficiency). As metabolic reprogramming from oxidative phosphorylation toward increased glycolysis is a hallmark of cancer cells; there is increasing evidence that the ketogenic diet may also be beneficial as an adjuvant cancer therapy by potentiating the antitumor effect of chemotherapy and radiation treatment. This article is part of a Directed Issue entitled: Energy Metabolism Disorders and Therapies.